Co-Authorship and Co-Occurrence Bibliometric Analysis of the Scientific Literature on Social Capital and Sports - Sahudi, Udi; Saputra, Yudha Munajat; Ma’mun, Amung; Nuryadi, Nuryadi; Sofyan, Davi (Department of Physical Education, Sport, Health and Recreation, 2022)
Sports are regarded as social activities. By defining the publication's descriptive parameters, illustrating the pattern of citations, extracting the author's keywords, and evaluating the research's performance on the social themes of capital and sports, this study intends to provide a thorough explication. Researchers can use this study's orientation to learn more about how scholarly publications on social capital and sports have developed. This study includes an orientation for researchers to better understand the progress of scientific publications related to social capital and sports. Data was obtained from the Scopus database of 529 documents from 1998 to 2022. Among 51 countries, scientists from the United Kingdom accounted for around 125 of the total international publications. In addition, Social Sciences is the subject area that publishes the most, namely 312 documents. Kondo, Katsunori, from Chiba University, Japan, is the author with the largest total link strength of 66. Social Capital is the keyword that appears the most, with 214 occurrences, and has a total strength of 233. Overall, it can be concluded that this field of study is expanding, with new techniques and directions being developed. Therefore, a thorough analysis of social capital and sport in numerous study fields can aid scholars and professionals in advancing future understanding in these fields.